Complementary and Alternative Medicine for Substance Use Disorders: A Scientometric Analysis and Visualization of Its Use Between 2001 and 2020 - Junyue, Jiao; Siyu, Chen; Xindong, Wang; Qinge, Xiao; Jingchun, Zeng; Liming, Lu; Guohua, Lin (Frontiers in Psychiatry, 2021)
Background: This study aimed to identify frontiers for further studies via brief understanding in complementary and alternative medicine (CAM) for substance use disorders (SUDs). Material and Methods: Publications on the use of CAM for treating SUDs were retrieved from the Web of Science Core Collection from 2001 to 2020 on 12 July, 2020, and visualized by CiteSpace V. Results: A total of 3,807 publications were obtained. The USA, China, and England were the leading research centers. However, India and Pakistan have recently focused on assessing CAM for the treatment of SUDs. Frederick L Altice was found to be the most productive author. Addiction ranked first among the frequently cited journals, which exceeded 1,000. The most common CAM therapies were acupuncture and CAM psychotherapies, such as mindfulness meditation. Conclusion: CAM is gaining attention globally for treating SUDs. CAM psychotherapy and acupuncture are hotspots and deserve further study. Researchers should strengthen peer cooperation in this field.